Canadian Journal for women in coaching
The Women in Coaching program is a national campaign to increase the number of coaching opportunities for women at all levels of sport in Canada. Since 1987, over 300 women coaches have received some $1,290,000 in the form of professional development grants, major Games apprenticeship grants, and National Coaching Institute scholarships. Recent groundbreaking projects include the Women in Coaching Long-Term Coaching Apprenticeship Program; Best Practices, a grant program recognizing women in coaching initiatives; and now, the Canadian Journal for Women in Coaching. The findings of preliminary focus groups, held in Montreal and Quebec City for active women coaches at all levels, played a central role in shaping the contents of the Journal. Additional workshops, which are open to women coaches at all levels, are currently being scheduled for the fall. These sessions, to be held at the National Coaching Institutes, will also influence content. An additional aspect of the campaign is the development of resources, such as the Women in Coaching section of the CAC Web site, to increase the public profile of women coaches at the international and professional levels as role models for aspiring coaches.